Dialogue Summary: Supporting Neighbourhood-Based Approaches to Addressing Poverty Concentration and its Impacts on Health in Hamilton - Lavis, JN; Dunn, James R. (My University, 2011)
A summary of what was learned from a stakeholder dialogue that addressed problems related to supporting neighbourhood-based approaches to addressing poverty concentration and its impacts on health, options for addressing these problems, key implementation considerations, and next steps for supporting neighbourhood-based approaches to addressing poverty concentration and its impacts on health in Hamilton.
Keywords: neighbourhood; poverty; health; Hamilton